Pengaruh Motivasi Dan Supervisi Kepala Sekolah Terhadap Peningkatan Penggunaan Media Audio Visual Pada Guru TK - Wageyati Asiseh; Rudy Sumiharsono; Eges Triwahyuni (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
The aim of the research was to determine whether there is an influence of school principal supervision on teaching motivation and increasing the use of audiovisual media among kindergarten teachers in the PAUD 02 Kalibaru cluster. The research design uses causal quantitative. The method for determining areas is purposive area sampling. The population research population research technique was 32 Kindergarten teachers in the PAUD 02 Kalibaru cluster. Data collection techniques: 1). observation, 2). documentary, 3). questionnaire, 4) interview. The interview results are then processed into several instrument tests from validity and reliability tests, then classic assumption tests including normality tests, homogeneity tests, autocorrelation tests, and heteroscedasticity tests, and finally hypothesis tests which include t tests and F tests. Effect of t test results. Principal Supervision on Teaching Motivation Audio Visual Media Together (3.254>3.33).